Genomic characterization of Pantoea anthophila strain UI705 causing urinary tract infections in China - Zhang, Yingmiao; Fan, Yue; Zhan, Yu; Wang, Hao; Li, Xun; Wang, Hui; Feng, Tian; Shi, Lifeng; Wang, Jing; Wang, Hui; Lu, Zhongxin (Frontiers in Cellular and Infection Microbiology, 2023)
Pantoea anthophila (P. anthophila) is gram-negative bacterium initially isolated from Impatiens balsamina in India. P. anthophila has been characterized with low pathogenicity, and no human infections caused by this organism have been reported yet.We report the first case of urinary tract infection caused by P. anthophila in a 73-yearold man after bladder cancer surgery. The bacterial isolate gained from urine was named UI705 and identified as P. anthophila by MALDI-TOF mass spectrometry. The genome sequencing and analysis were performed to further characterize the pathogenesis of the clinical isolate. To the best of our knowledge, this is the first report of human infection caused by P. anthophila in China. The draft genome sequence of P. anthophila UI705 provides a fundamental resource for subsequent investigation of its virulence factors, antibiotic resistance, host-pathogen interactions, as well as comparative genomics of genus Pantoea.